2015
DOI: 10.1002/aenm.201500111
|View full text |Cite
|
Sign up to set email alerts
|

Disorder‐Induced Open‐Circuit Voltage Losses in Organic Solar Cells During Photoinduced Burn‐In

Abstract: different effect on device performance depending on the morphology of the active layer. We investigate this infl uence of morphology in the context of two fundamental mechanisms that are able to cause a V oc loss. First, an increased trap-assisted recombination rate that lowers the charge carrier density [ 2,3 ] and second a broadening of the density of states that reduces V oc [ 4,5 ] with the same charge carrier density and unchanged recombination dynamics. Answering this question is important not only for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
160
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 59 publications
6
160
0
Order By: Relevance
“…The pulse intensity was controlled to keep the height of the photovoltage transient smaller than 10 mV resulting in a voltage transient with amplitude ΔV ≪ Voc. The measured transient decays show the form of single exponentials, as expected for the pseudo-first-order kinetic (Hamilton et al, 2010;Heumueller et al, 2015).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The pulse intensity was controlled to keep the height of the photovoltage transient smaller than 10 mV resulting in a voltage transient with amplitude ΔV ≪ Voc. The measured transient decays show the form of single exponentials, as expected for the pseudo-first-order kinetic (Hamilton et al, 2010;Heumueller et al, 2015).…”
supporting
confidence: 65%
“…As collected in Table 2 Understood the limitation in the transport properties, we then focus on the better ability of the ternary system in the photogeneration by employing charge extraction (CE) and photoinduced absorption (PIA) spectroscopy (Salvador et al, 2012;Löslein et al, 2013;Gasparini et al, 2015b). In CE measurements, the samples were connected to the terminal of an oscilloscope with the input impedance of 1 MΩ and illuminated with a continuous background laser to keep it in the Voc condition (Heumueller et al, 2015). In order to study the transient decay, we used a nanosecond switch that shifts the cell from open circuit to short circuit condition, allowing the calculation of charge density (n) by integrating the curves, respectively ( Figure 4A) (Heumueller et al, 2015;Gasparini et al, 2016 Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown severe deterioration of photovoltaic effi ciency down to 60% during the fi rst 100 h light exposure. [15][16][17][18][19] In other words, the burn-in photodegradation mechanism is still open question. Thus, it is highly required to understand the burn-in loss mechanism.…”
Section: Doi: 101002/aenm201600171mentioning
confidence: 99%
“…[30] In addition, McGehee and co-workers and Brabec and co-workers found that a high degree of crystallinity could significantly reduce the initial light-induced degradation, which is caused by light-induced traps. [37,44] Despite the remarkable thermal stability and photoinduced stability in these studies, the precise correlation between the molecular structure and device stability remains phenomenological, based on the reports for several thousands of photovoltaic materials. [12,18,[45][46][47] OSCs can be divided into two categories: polymer based and small molecule based devices.…”
mentioning
confidence: 99%